Similar prevalence of anxiety and depression symptoms in any ICU survivor patient relative - Shah, Ashutosh; Shah, Amita; Rathod, Darshana; Patel, Mayur; Hansora, Sanket (International Journal of Research in Medical Sciences, 2023)
Background: Iwashyna et al defined a chronic critically ill (CCI) patient as any patient requiring care in ICU for more than or equal to 10 days. Physicians often assume that the prevalence of anxiety and depression symptoms in relatives of CCI patients would be higher than in those patients who are not CCI. We hypothesized that there would be no difference in the prevalence of anxiety and depression symptoms of relatives of a CCI and those whose patients are not CCI. We aimed to establish that the prevalence of anxiety and depression symptoms are similar in relatives of any ICU survivor patient. Methods: The study was a non-interventional, observational, cross-sectional study. Relatives were evaluated as early as possible after day ten following ICU admission for CCI patients and non-CCI patients on or a day before discharge from ICU. During this evaluation, anonymous demographic data of relatives were captured, and PHQ-9 and GAD-7 scales were administered and completed by the relative. Results: A total of 418 relatives consented and were included in the study [104 in CCI patient group and 314 in non-CCI group]. Overall, the prevalence of anxiety and depression symptoms in the entire study cohort was 23.2% (95% CI, 19.4-27.5) and 16.5% (95% CI, 13.2-20.4), respectively. There was no statistical difference between the two groups in the proportion of PHQ-9 total score >9 (p value: 0.577) as well as the GAD-7 total score (p value: 0.816). Conclusions: There was no difference in the prevalence of anxiety and depression symptoms in relatives of a CCI versus those whose patients are not CCI.